2011
DOI: 10.4103/0973-1296.84237
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of the Phyllanthus species on tert-butyl hydroperoxide (t-BH)-induced cytotoxicity in HepG2 cells

Abstract: Background:Phyllanthus (Euphorbiaceae) species have long been used in folk medicine to treat various pathological conditions including liver diseases. Some species of Phyllanthus were found to exhibit hepatoprotective activity against drugs or toxins and this property was majorly attributed to phyllanthin and hypophyllanthin. In this study, we examined the hepatoprotective activity of five different species of Phyllanthus, namely, Phyllanthus amarus, Phyllanthus fraternus, Phyllanthus maderaspatensis, Phyllant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…[34] Number of medicinal plants has been reported with good hepatoprotective activity with potential antioxidative mechanism due to presence of flavonoids and phenolic compounds. [353637] The protective role of this plant against liver toxicity might be through antioxidative effect of flavonoids rich in the plant.…”
Section: Discussionmentioning
confidence: 99%
“…[34] Number of medicinal plants has been reported with good hepatoprotective activity with potential antioxidative mechanism due to presence of flavonoids and phenolic compounds. [353637] The protective role of this plant against liver toxicity might be through antioxidative effect of flavonoids rich in the plant.…”
Section: Discussionmentioning
confidence: 99%
“…An aqueous P. urinaria extract inhibits HBV replication and expression in a HBV transient transfection model in vitro (Wu et al, 2015 ). Sharma et al ( 2011 ) reported that a methanolic extract of P. urinaria whole plant protects the Hep G2 cell line against tert-butyl hydroxide (t-BH)-induced cytotoxicity. An ethanolic extract of P. urinaria whole plant attenuates the acetaminophen-induced hepatotoxicity and inhibition of the cytochrome P450 CYP2E1 enzyme in mice (Hau et al, 2009 ).…”
Section: Pharmacological Activities Of P Urinaria mentioning
confidence: 99%
“…It is the most important site of intermediary metabolism responsible for the detoxification and excretion of various substances like xenobiotics by altering and expelling toxins and wastes ( Chaudhari and Mahajan, 2016 ). Owing to continuous exposure to the toxicant via the portal blood circulation, the liver is highly susceptible to damage by xenobiotics, drugs, and hazardous substances ( Sharma et al, 2011 ). Due to handling the metabolism of various proteins, lipids, carbohydrates, secretion of bile, and storage of vitamins, it is considered as one of the most vital organs ( Bechmann et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%